ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGEMBALIAN KREDIT MIKRO UTAMA (KMU) PADA SEKTOR PERTANIAN OLEH DEBITUR BANK NTT KANTOR CABANG UTAMA KUPANG PROVINSI NUSA TENGGARA TIMUR - Solvi M. Makandolu; Johanes G. Sogen (JURNAL NUKLEUS PETERNAKAN, 2015)
Micro, Small and Medium Enterprises (MSMEs) have a very important role in the economy. A study applying a survey method approach was conducted in October 2012 - January 2013 to determine the factors that affect the rate of return on Prime Micro Credit (PMC) in agriculture on NTT Bank - Main Branch of Kupang. This study aims to: (1) describe the characteristics of the customers returning PMC and creditors performance in NTT Bank - Main Branch of Kupang, (2) determine assesment process of PMC and its distribution, and (3) analyze the factors that affect the collectibility of PMC in agriculture sector on NTT Bank - Main Branch of Kupang. The sampling method used was proportionate cluster purposive sampling. The number of samples used were 80 respondents which divided into 55 no smoothly customers and 25 smoothly customers. The data was analyzed using descriptive qualitative analysis and quantitative analysis. The quantitative analysis model used is a binary logistic regression. Quantitative data was processed using Microsoft Excel 2007 and SPSS version 18. The results showed that the characteristics of customers who are facing non performing loans are mostly no longer productive age, male, married, has the highest level of junior secondary education, as well as having a large number of family. Business characteristics that affect the level of noncurrent collectibility are amount of assets that is less than 20 million IDR, turnover of less than five million IDR, the credit of more than 30 million IDR, operating revenues less than one million IDR and the business done is not a core business but just as a companion of core business. Factors that are having significant effect on the collectability of micro credit were assets variable (<20 million), turnover (<5 million), credit limit (> 30 million), business income, back payment, paid-in interest and time period of repayment (P <0.10). The performance of NTT Bank in executing micro credit is classified into good performance. In order to reduce the number of customers were are not fluent in their credit worthiness, then micro credit disbursed should not more than 30 million IDR and the business involved should be as core business. ABSTRAK Usaha Mikro Kecil dan Menengah (UMKM) memiliki peran yang sangat penting dalam perekonomian. Suatu studi dengan pendekatan metode survei telah dilaksanakan pada bulan Oktober 2012 – Januari 2013 untuk mengetahui faktor-faktor yang mempengaruhi tingkat pengembalian Kredit Mikro Utama (KMU) di bidang pertanian pada Bank NTT Kantor Cabang Utama Kupang. Penelitian ini bertujuan untuk mengetahui proses penyaluran dan penilaian KMU dan mendeskripsikan karakteristik kreditur yang mempengaruhi tingkat pengembalian KMU di bidang pertanian dan peternakan pada Bank NTT Kantor Cabang Utama Kupang. Metode sampling yang digunakan adalah proportionate cluster purposive sampling. Jumlah sampel yang diambil sebanyak 80 orang debitur dimana 55 orang debitur tidak lancar dan 25 orang debitur lancar. Faktor-faktor yang secara signifikan berpengaruh terhadap kolektibilitas KMU Bank NTT ialah variabel aset (<Rp.20 juta), omset (<Rp.5 juta), plafon kredit (>Rp.30 juta), pendapatan usaha, setoran tunggakan, setoran bunga, dan waktu pelunasan (P<0.10). Kinerja Bank NTT dalam penyaluran kredit mikro utama tergolong baik. Dalam rangka menekan jumlah debitur yang tidak lancar dalam pengembalian kreditnya, maka sebaiknya KMU yang dikucurkan tidak boleh lebih dari Rp.30 juta dan bidang usaha yang digeluti tersebut harus menjadi usaha pokok.